Wind-Induced Vibration Control of High-Rise Structures Using Compound Damping Cables. (22nd April 2021) - Yu, Jianda; Duan, Zhibo; Zhang, Xiangqi; Peng, Jian
Abstract : Based on the vibration reduction mechanism of compound damping cables, this study focuses on the wind-induced vibration control of high-rise structures with additional mass at the top. The differential equation of motion of the system under the action of the composite damping cable is established, and the analytical solution of the additional damping ratio of the structure is deduced, which is verified by model tests. The vibration response of the structure under the action of simple harmonic vortex excitation and randomly fluctuating wind loads is studied, and the effect of different viscous coefficients of the dampers in the composite damping cable and different installation heights of the damping cable on the vibration control is analyzed. The results show that a small vortex excitation force will cause large vibrations of low-dampened towering structures, and the structure will undergo buffeting under the action of wind load pulse force. The damping cable can greatly reduce the amplitude of structural vibration. The root means square of structural vibration displacement varies with damping. The viscosity coefficient of the device and the installation height of the main cable of the damping cable are greatly reduced.